Pengaruh Integrasi Flashcard Digital dan Model Kooperatif Tipe Teams Games Tournament terhadap Hasil Belajar IPA Materi Ekologi dan Keanekaragaman Hayati - Pramudya Aulia Fadila; Muhamad Arif Mahdiannur (Pustaka Digital Indonesia, 2026)
This study aims to investigate the differences in learning outcomes between classes using digital flashcard media assisted by QR codes with the TGT cooperative model compared to classes that did not receive the treatment. This study used a quantitative approach with a quasi-experimental design, specifically a pretest-posttest non-equivalent control group design. The subjects of this study consisted of two classes of seventh-grade students at SMP Negeri 48 Surabaya in the even semester of the 2025/2026 academic year. The finding indicate three variables. Research data were collected through written test methods and observations. The results of the pretest and posttest were analyzed through descriptive statistics, normality testing, homogeneity of variance testing, independent t-tests, and effect size calculations using Cohen's d. Meanwhile, observation data regarding learning implementation were evaluated by calculating the percentage of achievement of each indicator. The research findings showed that the average posttest score in the experimental group was above the control group. The results of the independent t-test confirmed a significant difference with a significance value lower than the 0.05 limit. The measurement of effect size using Cohen's d was included in the high category. Observations of the learning process showed that the average overall percentage for both groups was in the very good category. These finding indicate that the learning process in both classes was carried out effectively, with no differences in the quality of classroom management. Thus, this finding implies that the integration of the TGT model with digital flashcard media can be used as an effective learning alternative to improve student learning outcomes. Suggestions that need to be considered, namely the research process can be conducted in more than two meetings, to reduce time constraints. Future research can also apply other science materials that can still be adapted to the TGT learning model and digital flashcard media simultaneously.